(untitled) (KULT_online, 2017)
The handbook Lesen. Ein interdisziplinäres Handbuch, edited by Ursula Rautenberg and Ute Schneider, offers an interdisciplinary overview of different scientific approaches to reading as a cultural technique. The book presents both current research perspectives and methods as well as institutions and organizations related to reading. As a last point, reading is put into some of its functional connections. The book can be used as both an access point to different aspects of the topic and also as a means to establish relations between different disciplinary approaches.